Corrosion-resistant metal protection liquid as well as preparation method and application thereof
By electrochemical deposition of cerium-containing compounds, alkenylthiourea and 4-carboxypropimidazole modified film layers, the corrosion problem of stainless steel in harsh environments is solved, and efficient corrosion resistance is improved and cost reduction is achieved. Practical and cost-effective.
Patent Information
- Application Number
- CN202411547725.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-10
AI Technical Summary
Stainless steel is susceptible to attacks by corrosive ions such as chloride ions in harsh environments, especially in marine environments, resulting in cracking and corrosion of the surface passivation film. In the prior art, chromic acid is highly toxic and environmentally polluted. Although rare earth ion salt solution is environmentally friendly, The cost is high, and the stability of traditional coatings in extreme environments is insufficient.
The cerium-containing compound is deposited on the surface of stainless steel by electrochemical means, and the film layer is modified with alkenylthiourea and 4-carboxypropimidazole to form a tight protective film, reducing the amount of cerium, improving corrosion resistance and sustained release efficiency.
It significantly improves the corrosion resistance of stainless steel, especially on the premise of reducing the cerium content, improves the hydrophilicity and sustained release efficiency of the film layer, has high practical cost performance, and enhances the kinetic stability of stainless steel in extreme environments.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to a corrosion-resistant metal protective liquid, a preparation method and application thereof, and belongs to the field of metal corrosion-resistant protection. Background Art
[0002] Stainless steel refers to a corrosion-resistant iron-based alloy containing 12-30% chromium. It is widely used in many fields such as national defense science and technology, aerospace, marine exploration, metallurgical manufacturing, mechanical transportation, construction, food and medical treatment, and is an alloy material that plays an important role in the development of the national economy. Stainless steel has high corrosion resistance, but the corrosion resistance of stainless steel is still greatly challenged under harsh environmental conditions, especially in the marine environment. Due to the action of corrosive ions such as chloride ions, the passivation film on the surface of stainless steel is easily attacked and ruptured, causing severe corrosion of the exposed stainless steel matrix.
[0003] The main forms of stainless steel corrosion include galvanic corrosion, intergranular corrosion, crevice corrosion and pitting corrosion. Galvanic corrosion is corrosion caused by different surface potentials of metals when different phases of metals come into contact. When galvanic corrosion occurs, a galvanic current flows from the anode to the cathode, causing the anode metal with a lower potential to be rapidly consumed and causing severe corrosion, while the cathode metal is protected. Intergranular corrosion is the process of crack growth between the crystal structures inside the metal matrix phase. The difference in chemical composition between metal grains and impurities or internal stress at the grain boundaries cause corrosion to occur preferentially at the grain boundaries, destroying the bonding force of the metal grains and significantly reducing the inherent mechanical properties of the metal. Crevice corrosion is a form of corrosion that occurs in the gaps between metals or non-metals. It is quite universal. Almost all metals may experience crevice corrosion under conditions that are sensitive to crevice size. The lack of oxygen in the crevice forms a local anode, and the crevice metal dissolves. Pitting is one of the main forms of stainless steel corrosion. It is highly concealed, difficult to detect, has a fast corrosion rate, and is highly dangerous. It is extremely sensitive to medium environments containing halogen ions such as chlorine, bromine, and iodine. Stainless steel pitting can be divided into two stages: pitting nucleation and pitting growth. Pitting nucleation occurs preferentially at grain boundaries, heterogeneous structures, inclusions, etc., generating pitting holes with a diameter of several microns, and corrosion products cover the pits. The stainless steel surface outside the pits becomes the cathode due to sufficient oxygen supply, while the inside of the pits becomes the anode due to lack of oxygen, eventually forming a closed corrosion cell with self-catalytic effect. The pits grow rapidly in a specific direction inside the stainless steel. In severe cases, corrosion perforation can be caused, which is extremely dangerous.
[0004] Stainless steel corrosion protection technology mainly includes rare earth ion impregnation, organic coating protection, graphene layer modification, and surface passivation technology. Although traditional chromic acid passivation can significantly improve the corrosion resistance of stainless steel, extend the service life of stainless steel, and has good results, chromic acid is extremely toxic and seriously pollutes the environment, and its use is strictly restricted. Rare earth ion salt solutions are non-toxic and harmless, environmentally friendly, and can replace chromic acid to a certain extent. Among them, cerium ions are more commonly used. For example, the prior art uses a mixed solution of cerium nitrate, citric acid, and hydrogen peroxide to prepare a new cerium chemical conversion film on the surface of 316L stainless steel through a chemical immersion method. The pitting potential of stainless steel in 72°C concentrated seawater is greatly improved, and the pitting resistance is significantly enhanced. The prior art contains a method of immersing stainless steel in a solution containing Ce. 3+ In a solution of 3.5wt.% NaCl, a golden cerium conversion coating was obtained on the surface of 304 stainless steel. The corrosion resistance of stainless steel in 3.5wt.% NaCl solution was significantly improved, the passivation current density was reduced by about one order of magnitude, and both cathode and anode reactions were inhibited to a certain extent.
[0005] Organic coating protection is to coat an organic protective layer on the surface of stainless steel to isolate the corrosive medium from contact with stainless steel, so as to protect the stainless steel substrate from corrosion damage. Polyaniline is an important conductive polymer, widely used in sensors, transparent conductors, electrochromic displays, etc. It is also used in corrosion protection coatings. For example, silane is an organic reagent with good adhesion. It can form an organic film on the surface of stainless steel through hydrolysis and dehydration condensation reactions to isolate the material from the external environment. Adding it to the material can also improve the metal dispersion, strength, elongation and other mechanical properties. Silanization treatment is green and environmentally friendly, simple to operate, has good adhesion and strong corrosion resistance. It is widely used in aerospace, seabed survey, precision parts manufacturing and other departments. For example, a double-layer coating of silane and polyparaxylene synergistically prepared on the surface of 316L stainless steel shows good protective properties in solution.
[0006] Graphene layer modification: Graphene is composed of carbon atoms arranged in a hexagonal lattice, and each carbon atom is bonded to the three most adjacent carbon atoms in the plane through sp2 hybrid orbitals to form high-strength carbon bonds. Graphene (without defects) is the strongest material found so far in mechanical properties. Impermeability to gases and salts makes graphene the best choice for corrosion protection. Graphene's excellent conductivity and high specific surface area play an important role in its corrosion resistance. Graphene can make the permeation path of corrosive media through the coating to the metal surface more tortuous. It plays an excellent barrier role for water, oxygen and other corrosive media. For polymer anti-corrosion coatings, when corrosion begins to occur at the metal / coating interface, the electrons generated by the anode reaction migrate to the cathode area through the metal conductor, participate in the cathode reaction, and complete the corrosion process. Once corrosion begins at the interface between metal and traditional insulating coatings, it is difficult to stop. However, when functionalized graphene is incorporated into the coating, due to its excellent conductivity, an alternative path for electrons is provided, making it difficult for electrons to reach the cathode position.
[0007] Surface passivation technology: The passive film spontaneously generated on the surface of stainless steel in the air is the fundamental reason why stainless steel has corrosion resistance. The composition, structure and physical state of the passive film are the main factors affecting the performance of the passive film. By optimizing and reconstructing the passive film on the surface of stainless steel through surface passivation technology and regulating and improving the physical and chemical properties of the passive film, the corrosion resistance of stainless steel can be effectively improved. Stainless steel surface passivation technology is to chemically or electrochemically treat stainless steel in a specific medium to form a passivation film with specific structure and properties on its surface, enhance the kinetic stability of stainless steel in extreme environments, and inhibit the occurrence of local corrosion. At present, the commonly used surface passivation technology is mainly nitric acid passivation. Summary of the invention
[0008] The present invention provides a corrosion-resistant metal protective liquid, and a preparation method and application thereof. By electrochemical means, a cerium-containing compound is deposited on the surface of stainless steel metal, which can effectively improve the corrosion resistance of stainless steel. In particular, under the premise of reducing the amount of cerium content, alkenyl thiourea and 4-carboxybenzamidazole are used to modify the deposited film layer, thereby improving the sustained release efficiency, and having extremely high practical cost performance. Specifically: A corrosion-resistant metal protective liquid consists of no more than 0.015 mol / L of cerium chloride, 0.1-0.2 mol / L of myristic acid, 7-12 mmol / L of propylene thiourea, 3-4 mmol / L of 4-carboxybenzalimidazole and deionized water.
[0009] A corrosion resistant metal protective liquid is used by the following steps: (1) preparing a protective solution: the protective solution is composed of no more than 0.015 mol / L cerium chloride, 0.1-0.2 mol / L myristic acid, 7-12 mmol / L propylene thiourea, 3-4 mmol / L 4-carboxybenzalimidazole and deionized water; (2) Electrodeposition of corrosion-resistant coating: With an inert metal sheet as anode and a metal sheet as cathode, electrodeposition was performed at 20-25°C, stirring speed 100-200 rpm, and 5-20 V for 5-15 min; (3) Post-treatment: Wash with ethanol and deionized water in sequence, and dry at 50-60°C.
[0010] The concentration range of the cerium chloride is 0.01-0.015 mol / L.
[0011] The metal sheet is a stainless steel sheet.
[0012] The cathode and anode are parallel to each other, and the distance between the electrodes is 2-3 cm.
[0013] A corrosion-resistant coating material is obtained by treating a stainless steel metal material with a corrosion-resistant metal protective liquid.
[0014] An application of a corrosion-resistant metal protective liquid deposits cerium compounds on the surface of stainless steel metal by electrochemical means.
[0015] The basic reaction principle of the present invention is 2Ce 3+ +6CH3(CH2) 12 COOH+6e - =2Ce(CH3(CH2) 12 COO)3+3H2, among which propylene thiourea and 4-carboxybenzimidazole can form a relatively close adsorption with the metal substrate, thereby obtaining a more complete protective film, thereby improving its corrosion resistance.
[0016] Beneficial technical effects: The present invention can effectively improve the corrosion resistance of stainless steel by electrochemically depositing cerium-containing compounds on the surface of stainless steel metal, especially under the premise of reducing the amount of cerium content, using alkenyl thiourea and 4-carboxybenzalimidazole to modify the deposited film layer, thereby improving the hydrophilicity of the film layer and further improving the sustained release efficiency, and has extremely high practical cost performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Attached Figure 1 Polarization curves of the embodiments of the present invention and the comparative examples.
[0018] Attached Figure 2 Impedance test of the embodiments of the present invention and the comparative examples.
[0019] Attached Figure 3 Impedance Bode plots of the embodiments of the present invention and the comparative example.
[0020] Attached Figure 4 Hydrophobicity of the Examples of the present invention and the Comparative Examples. DETAILED DESCRIPTION Example 1
[0021] A corrosion resistant metal protective liquid is used by the following steps: (1) preparing a protective solution: the protective solution is composed of 0.01 mol / L cerium chloride, 0.1 mol / L myristic acid, 7 mmol / L propylene thiourea, 3 mmol / L 4-carboxybenzalimidazole and deionized water; (2) Electrodeposition of corrosion-resistant coating: using an inert metal sheet as anode and a stainless steel sheet as cathode, electroplating was performed at 20°C, stirring speed 100 rpm, 7 V for 5 min. The cathode and anode were parallel to each other and the electrode spacing was 2 cm. (3) Post-treatment: Wash with ethanol and deionized water in sequence, and dry at 50°C. Example 2
[0022] A corrosion resistant metal protective liquid is used by the following steps: (1) preparing a protective solution: the protective solution is composed of 0.0125 mol / L cerium chloride, 0.15 mol / L myristic acid, 9.5 mmol / L propylene thiourea, 3.5 mmol / L 4-carboxybenzalimidazole and deionized water; (2) Electrodeposition of corrosion-resistant coating: With an inert metal sheet as anode and a stainless steel sheet as cathode, electrodeposition was performed at 22.5°C, stirring speed 150 rpm, 12.5 V for 10 min. The cathode and anode were parallel to each other, and the electrode spacing was 2.5 cm. (3) Post-treatment: Wash with ethanol and deionized water in sequence, and dry at 55°C. Example 3
[0023] A corrosion resistant metal protective liquid is used by the following steps: (1) preparing a protective solution: the protective solution is composed of 0.015 mol / L cerium chloride, 0.2 mol / L myristic acid, 12 mmol / L propylene thiourea, 4 mmol / L 4-carboxybenzalimidazole and deionized water; (2) Electrodeposition of corrosion-resistant coating: using an inert metal sheet as anode and a stainless steel sheet as cathode, electroplating was performed at 25°C, stirring speed 200 rpm, 20 V for 15 min. The cathode and anode were parallel to each other and the electrode spacing was 3 cm. (3) Post-treatment: Wash with ethanol and deionized water in sequence, and dry at 60°C.
[0024] Comparative Example 1 is a blank stainless carbon steel, which is washed with acetone, ethanol and deionized water in sequence before use. All the examples and comparative examples are subjected to the above surface pretreatment to fully protect the surface of the stainless steel and avoid the influence of surface impurities.
[0025] Comparative Example 2 A corrosion-resistant metal protective liquid is used by the following steps: (1) Preparing a protective solution: The protective solution is composed of 0.0125 mol / L cerium chloride, 0.15 mol / L myristic acid, and deionized water; (2) Electrodeposition of corrosion-resistant coating: With an inert metal sheet as anode and a stainless steel sheet as cathode, electrodeposition was performed at 22.5°C, stirring speed 150 rpm, 12.5 V for 10 min. The cathode and anode were parallel to each other, and the electrode spacing was 2.5 cm. (3) Post-treatment: Wash with ethanol and deionized water in sequence, and dry at 55°C.
[0026] Comparative Example 3 A corrosion-resistant metal protective liquid is used by the following steps: (1) preparing a protective solution: the protective solution is composed of 0.0125 mol / L cerium chloride, 0.15 mol / L myristic acid, 9.5 mmol / L propylene thiourea, and deionized water; (2) Electrodeposition of corrosion-resistant coating: With an inert metal sheet as anode and a stainless steel sheet as cathode, electrodeposition was performed at 22.5°C, stirring speed 150 rpm, 12.5 V for 10 min. The cathode and anode were parallel to each other, and the electrode spacing was 2.5 cm. (3) Post-treatment: Wash with ethanol and deionized water in sequence, and dry at 55°C.
[0027] Comparative Example 4 A corrosion-resistant metal protective liquid is used by the following steps: (1) preparing a protective solution: the protective solution is composed of 0.0125 mol / L cerium chloride, 0.15 mol / L myristic acid, 3.5 mmol / L 4-carboxybenzalimidazole and deionized water; (2) Electrodeposition of corrosion-resistant coating: With an inert metal sheet as anode and a stainless steel sheet as cathode, electrodeposition was performed at 22.5°C, stirring speed 150 rpm, 12.5 V for 10 min. The cathode and anode were parallel to each other, and the electrode spacing was 2.5 cm. (3) Post-treatment: Wash with ethanol and deionized water in sequence, and dry at 55°C.
[0028] Comparative Example 5 A corrosion-resistant metal protective liquid is used by the following steps: (1) preparing a protective solution: the protective solution is composed of 0.08 mol / L cerium chloride, 0.15 mol / L myristic acid, 9.5 mmol / L propylene thiourea, 3.5 mmol / L 4-carboxybenzalimidazole and deionized water; (2) Electrodeposition of corrosion-resistant coating: With an inert metal sheet as anode and a stainless steel sheet as cathode, electrodeposition was performed at 22.5°C, stirring speed 150 rpm, 12.5 V for 10 min. The cathode and anode were parallel to each other, and the electrode spacing was 2.5 cm. (3) Post-treatment: Wash with ethanol and deionized water in sequence, and dry at 55°C.
[0029] Experimental tests were performed on Examples 1-3 and Comparative Examples 1-5. Figure 1 The corresponding polarization curve fitting parameters are shown in the following table.
[0030]
[0031] The following conclusions can be drawn directly and without doubt from the above table: (1) Example 2 has the lowest corrosion current density, that is, the best corrosion resistance. (2) Propylene thiourea and 4-carboxybenzalimidazole have a significant effect on corrosion resistance, and neither of them has a combined effect. (3) When the amount of cerium chloride, a precursor of cerium oxide, is too large, it has a significant adverse effect on the corrosion resistance of aluminum alloy, which may be related to irregular deposition or deposition morphology. Example 2 has the highest sustained release efficiency of 97.5%.
[0032] See attached Figure 2 and attached Figure 3 Impedance test, use software to Figure 2 and attached Figure 3 Impedance analysis, in the equivalent circuit, R S is the solution resistance, R ct is the charge transfer resistance, and CPE is the constant phase angle element related to the capacitance. The impedance value of the constant phase angle element CPE, i.e., the interface double layer capacitance C dl It can be calculated by the following formula: C dl =(Y0R ct 1-n ) 1 / n .
[0033]
[0034] According to the fitting results in the above table, it can be seen that after adding allylthiourea and 4-carboxybenzalimidazole at the same time in Example 2, the impedance of the system increases and the corresponding protective film is more complete. Figure 4In the hydrophobic test, comparative example 1 is blank carbon steel, and its contact angle to water is 45°, while comparative example 2 only deposits cerium compounds, which is a hydrophobic surface, and the contact angle is 115.5°. In comparison, the hydrophobicity of comparative examples 3-4 is reduced, that is, propylene thiourea and 4-carboxybenzalimidazole have hydrophilic improvement, while Example 2 is 91.7°C, which is located at the boundary range between hydrophilic and hydrophobic, and does not have super hydrophobicity, which may also be a reason why the present invention has corrosion resistance.
[0035] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A corrosion-resistant metal protective liquid, characterized in that The protective liquid consists of no more than 0.015 mol / L cerium chloride, 0.1-0.2 mol / L myristic acid, 7-12 mmol / L propylene thiourea, 3-4 mmol / L 4-carboxylbenzalimidazole and deionized water.
2. A corrosion-resistant metal protective liquid as claimed in claim 1, characterized in that Use it by following the steps below: (1) preparing a protective solution: the protective solution is composed of no more than 0.015 mol / L cerium chloride, 0.1-0.2 mol / L myristic acid, 7-12 mmol / L propylene thiourea, 3-4 mmol / L 4-carboxybenzalimidazole and deionized water; (2) Electrodeposition of corrosion-resistant coating: With an inert metal sheet as anode and a metal sheet as cathode, electrodeposition was performed at 20-25°C, stirring speed 100-200 rpm, and 5-20 V for 5-15 min; (3) Post-treatment: Wash with ethanol and deionized water in sequence, and dry at 50-60°C.
3. A corrosion-resistant metal protective liquid as claimed in claim 2, characterized in that The concentration range of the cerium chloride is 0.01-0.015 mol / L.
4. A corrosion-resistant metal protective liquid as claimed in claim 2, characterized in that The metal sheet is a stainless steel sheet.
5. A corrosion-resistant metal protective liquid as claimed in claim 2, characterized in that The cathode and anode are parallel to each other, and the distance between the electrodes is 2-3 cm.
6. A corrosion-resistant coating material, characterized in that The coating material is obtained by treating a stainless steel metal material with a corrosion-resistant metal protection liquid according to any one of claims 1 to 5.
7. An application of a corrosion-resistant metal protective liquid, characterized in that The corrosion-resistant metal protection liquid according to any one of claims 1 to 5 is used to deposit cerium compounds on the surface of stainless steel metal by electrochemical means.